DISHARMONI KEBIJAKAN PENGENAAN PBB-P2 PADAYAYASAN PENDIDIKAN (SEKOLAH MENENGAHKEJURUAN) DI KOTA BOGOR - Shabika Azzaria Putri (2022)
This study is to analyze the policy of the Bogor City Government regarding PBBP2 and the publics response to the policy of imposing PBB-P2. The problem in this study is the difference in the collection of PBB-P2 at the central and regional levels at educational foundations in Bogor City. This study use a normative juridical method which is supported by empirical data (interview) with Bapenda Bogor City and educational foundations. The results of the study obtained by the regional regulations and the regulations of the mayor of Bogor regarding PBB-P2 and its reduction are in fact different. In Practice, there are still educational foundations that pay PBB-P2 in full even though the land is owned in the nama of the foundation. The conclusions obtained from this study, the principle of Lex Superior Derogat Legi Inferiori, Bogor City regulations were formed to provide relief in terms of reducing PBB-P2 in vocational high school education foundations. The principle of distribution of PBB-P2 tax wasin fact implemented in 2011 which was previously the authority of the central government and wasn‟t imposed on educational foundations so that PBB-P2 was evenly distributed because it was already borne by the central government, because PBB-P2 is subject to waivers as stated in Mayor Regulation Number 18 of 2017, but there are educational foundations that are subject to PBB-P2 with full payment when in fact both the land is in the name ownership of the foundation for the imposition of PBB-P2. Keywords: PBB-P2, Foundation, Education, Regional Regulation